Strategi Peningkatan Kualitas Pelayanan Rumah Sakit ST. Carolus Borromeus Berdasarkan Indikator Mutu Rumah Sakit - Soedarmadji, Herly; Minggu Mere, Dominikus; A. Manafe, Henny; Man, Stanis; Perseveranda, M. E.; Ola Langoday, Thomas (Jurnal Ilmu Manajemen Terapan, 2023)
Referring to hospital quality indicators, which intend to find out the description or influence individually or simultaneously on the quality of hospital services by applying the quality indicators of St. Carolus Borromeus Hospital. This study uses a mix of methods, namely quantitative and qualitative with a sample of 40 people including management, unit heads, committee chairs, and team leaders. The results obtained make it clear if individually the strengths, weaknesses, and opportunities have an impact on service quality. Threat variable without affecting the quality of hospital services. Simultaneous influence of the variables of strengths, weaknesses, opportunities, and threats to improving the service quality of St. Carolus Borromeus Hospital Kupang. Alternative strategies to maximize service quality, such as hospitals seeking full-time specialist doctors, implementing online queues, monitoring and evaluating SOPs related to outpatient services (outpatient waiting time), and monitoring and evaluating of SPOs related to inpatient services (specialist doctor visiting hours) ) St. Charles Borromeus Hospital.